Novel regulatory role of non-coding RNAs in ankylosing spondylitis - Fang, Yanyan; Liu, Jian (Frontiers in Immunology, 2023)
Ankylosing spondylitis (AS) is a type of arthritis that primarily affects the spine and involves disorders of the immune and skeletal systems. However, the exact pathogenesis of AS is not fully understood. Non-coding RNAs (ncRNAs), particularly, long non-coding RNAs (lncRNAs), circular RNAs (circRNAs), and micro RNAs (miRNAs) and their interactions have been shown to influence many biological processes such as inflammatory responses, osteogenic differentiation and apoptosis, pyroptosis, and proliferation. In addition, ncRNAs reflect the disease activity of AS. In this review, we discuss the regulatory roles of ncRNAs in AS cell functions (inflammatory responses, cellular osteogenic differentiation and apoptosis, pyroptosis, and proliferation) and their potential applications in AS diagnosis and treatment. Understanding the role of ncRNAs in the pathogenesis of AS will lay the foundation for exploring potential new therapeutic approaches for AS.